Bilateral fusion of permanent canine and lateral incisor - Singh, VP; Dhital, S; Babu, TP Shankar; Agarwal, M (Health Renaissance, 2011)
Fusion is described as the union of two or more tooth buds. It is characterized by a reduced number of teeth , when fused tooth is counted as one . The prevalence of fused teeth in primary dentition is below 1% and even more less in permanent dentition. The occurrence of fusion in primary dentition may be followed by dental anomalies in permanent dentition. This case report presents a case of bilateral fusion of lateral incisor and canine in primary dentition which was followed by similar fusion in permanent dentition. The aim of this report is to highlight the rarity of such condition by virtue of the number of such cases reported in literature and to evaluate their pulpal morphologies to understand the type of fusion and presence of any other associated pathologies. Keywords: dental anamoly; fusion; gemination DOI: http://dx.doi.org/10.3126/hren.v9i2.4987 Health Renaissance 2011: Vol.9 (No.2): 122-124